Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.3 Exercises: 1


The derivative is $4x^3-12x^2+6x-12$.

Work Step by Step

Product Rule: $g'(x)=((u(x)(v(x))’=u'(x)v(x)+u(x)v’(x))$ $u(x)=(x^2+3) ;u’(x)=(2x) $ $v(x)=(x^2-4x) ;v’(x)=(2x-4) $ $g'(x)=(2x)(x^2-4x)+(x^2+3)(2x-4)=$ $(2x^3-8x^2)+(2x^3+6x-4x^2-12)=$ $4x^3-12x^2+6x-12$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.